Pengaruh Faktor Sosial Ekonomi Terhadap Kunjungan Antenatal Care di PMB Iis Musliha Tangerang Tahun 2024 - Elfira Sri Futriani; Ika Bela (Universitas Pahlawan Tuanku Tambusai, 2025)
Several factors that cause pregnant women to be less compliant in carrying out Antenatal Care (ANC) regularly and on time are their low socio-economic level. Socioeconomic factors play an important role in determining pregnant women's access to ANC services, with mothers' income, employment and education influencing their ability to receive quality health care. Economic constraints, such as transportation and inspection costs, are often the main barrier. To determine the influence of socio-economic factors on antenatal care visits at PMB Iis Musliha. This research uses quantitative descriptive research with a cross sectional study approach, the sample in this study was 40 pregnant women, chi square statistical analysis test. There is an influence of socio-economic factors on antenatal care visits with a value of p=0.000. Pregnant women with low socioeconomic status can seek support from family, friends or community groups to facilitate access to health services.